Frequency of branching pattern variation of the renal artery in a subset of Karachi population: A Study on Multi-Detector Computed Tomography - Mohiuddin, Maria; Khan, Rosheena Nabeel; Ahmed, Syeda Bushra; Lakhani, Mubina; Sughra, Amatul; Hassan, Nuzhat (Journal of Rawalpindi Medical College, 2024)
Abstract Objective: This study was conducted to determine the frequency of early branching patterns of renal arteries in a subset of Karachi. Method: This was a cross-sectional study, conducted in Ziauddin University Hospital, Clifton campus, Karachi. This was a prospective study conducted from June 2017 to July 2018. The sample size was calculated by using a 95 % confidence interval and study participants were included through consecutive sampling. A total of 250 participants (500 kidneys) aged 21 to 60 years and serum creatinine of ≤ 1.3 mg /dl were included in the study. All CT examinations were performed on an MDCT scanner (Alexion 16 slicer, Japan) in the arterial phase. Results: In this study, among a total of 250 study participants, 52 % (129 out of 250) were males and 48 % (121 out of 250) were females. Out of a total of 250 study participants, renal artery variation of pre-hilar early branching was found to be 9.2% (23) in individuals. On the right side early was found to be 4% and 5.2%. The length of the main renal artery in early branching measured was 11.0 ± 2.05 mm. Conclusion: This study concluded that the frequency of early branching of renal arteries was 9.2% in a subset of the Karachi population.